(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
Clastic deposits from the upper part of the Promina Beds, situated at the top of Promina Mt. (External-Karst Dinarides) in Croatia, were investigated. The aim of this study is to present and promote geological peculiarities of the Promina Mt. and its surroundings. Sedimentary succession in the study area comprises 3 lithofacies types, as the main findings of this study: carbonate conglomerates, calcarenites and calcareous mudstones. The results obtained by the combined field recording of the sedimentary succession and micropetrography are presented in the lithological column PRO-21, showing the determined lithofacies types and their characteristics. Attributed shelf to delta sedimentary environments were further discussed.